PUBLIC LICENSES IN THE DIGITAL ENVIRONMENT: ISSUES APPLICATION IN UKRAINIAN LAW - Stadnyk O.I. (Taras Shevchenko National University of Kyiv, 2024)
The article is devoted to the analysis of the legal regulation of public licenses in Ukraine, such as Creative Commons, GNU General Public License, and Apache Public License, which are actively used to regulate access to copyright objects in the digital environment. The article examines the characteristics and legal nature of public licenses, as well as the main challenges that arise during their implementation in Ukrainian legislation. Attention is drawn to the fact that the existing legislative acts, particularly the Law of Ukraine "On Copyright and Related Rights" and the provisions of the Civil Code of Ukraine, do not take into account the specifics of public licenses, complicating their practical application.The article also analyzes possible ways to regulate these legal relations through analogies with copyright agreements and licensing agreements, as well as the legal obstacles that may arise with such an approach. The author concludes on the necessity of reviewing and adapting Ukrainian legal acts to better regulate public licenses, as well as the potential for developing new legislative approaches that would better consider the specifics of electronic distribution of copyright objects and promote their effective use in Ukraine.

Стаття присвячена аналізу правового регулювання публічних ліцензій в Україні, таких як Creative Commons, GNU General Public License та Apache Public License, які активно використовуються для регулювання доступу до об'єктів авторського права в цифровому середовищі. У статті розглядаються особливості та правова природа публічних ліцензій, а також основні труднощі, що виникають при їх імплементації в українське законодавство. Акцентується увага на тому, що існуючі законодавчі акти, зокрема Закон України «Про авторське право і суміжні права» та положення Цивільного кодексу України, не враховують специфіки публічних ліцензій, що ускладнює їх застосування на практиці.У статті також аналізуються можливі шляхи врегулювання цих правовідносин за допомогою аналогії з авторськими договорами та ліцензійними договорами, а також розглядаються правові перешкоди, які можуть виникнути при такому підході. Автор робить висновок про необхідність перегляду та адаптації українських нормативно-правових актів для більш адекватного регулювання публічних ліцензій, а також можливість розробки нових законодавчих підходів, які б краще враховували специфіку електронного розповсюдження об'єктів авторського права і сприяли б їх ефективному використанню в Україні.
ПУБЛІЧНІ ЛІЦЕНЗІЇ В ЦИФРОВОМУ СЕРЕДОВИЩІ: ПРОБЛЕМИ ЗАСТОСУВАННЯ В УКРАЇНСЬКОМУ ПРАВІ
Keywords: public licenses; Creative Commons; GNU General Public License; Apache Public License; copyright; civil law; digital environment; legal regulation; Ukraine; digitalization; e-commerce.; публічні ліцензії; Creative Commons; GNU General Public License; Apache Public License; авторське право; цивільне право; електронне середовище; правове регулювання; Україна; цифровізація; електронна комерція.